DIRECTOR'S NATIONALITY DIVERSITY AND COMPANY PERFORMANCE: THE EVIDENCE FROM EMERGING MARKET - Zaitul Zaitul; Desi Ilona; Hafizah Abd-Mutalib; Eugene Okyere-Kwakye (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
This study describes the diversity of directors' nationality from company attributes: company leverage, growth, size, age, and sub-sector. This study also analyses the association between directors' nationality diversity and the performance of Indonesia's listed companies using two measurements: ROA and ROS (accounting performance) and Stock return and Tobin’s Q (market performance). This study used 3,290 observations in 235 companies (from 2004 to 2017). As a result, the level of director nationality diversity varies based on the company size (large vs. small), company age (old vs. young), company growth (high vs. low), company leverage (high vs. low), company sub-sector (central vs. manufacturing vs. trading & service sub-sector). In addition, the diversity of the supervisory board nationality is negatively related to the ROA and Tobin’s Q and positively associated with stock return. The company breaks the negative effect of supervisory board nationality diversity by reducing the periods foreign directors need to familiarise themselves with newly discovered circumstances, such as culture, systems, and language. The company suggests increasing the supervisory board nationality diversity regarding the stock return as detailed theoretical and practical implications.